The relationship between job satisfaction and job performance among employees in beverage industries in Negeri Sembilan - Selva Ganapathy, Arnachalam (2016)
This study was conducted in order to find any relationship between job satisfaction and job performance among employees in beverages industries in Negeri Sembilan. The job satisfaction dimensions that were surveyed in this study are promotion, salary, performance appraisal system and training and developmental programme. Vitaton (M) Sdn.Bhd, Bioton Corporation Sdn.Bhd, Vitatrade (M) Sdn.Bhd and Vita-Cool (M) Sdn.Bhd’s employees were the respondent of this study. The respondents were obtained from the human resource department of the said organisations. A total of 253 questionnaires were distributed to obtain the primary data used for this study. Both descriptive and inferential statistics were employed by researcher to find results. The results show that, training and developmental programme have very high influence on employee’s job performance and followed by performance appraisal system, salary and promotion. The R square value in model summary, researcher find that, job satisfaction dimension only influence 66.40% towards employee’s performance while remaining 33.60% were influence by other factors which is not discussed in this study. Recommendations for future study are to focus on other factors that might influence on employee’s job performance.